“Narrative images” as a learning approach: (transformative) adaptation scenarios for dealing with urban water risks in Hamburg, Germany - Hanf, Franziska S.; Meier, Linda; Hawxwell, Tom; Oßenbrügge, Jürgen; Knieling, Jörg; Sillmann, Jana (Frontiers in Sustainable Cities, 2024)
In recent years, weather-related extreme events have shown the limits of technical approaches to urban water challenges and highlighted the urgent need to rethink the relationship between cities and water and to see water as a partner in shaping transformative, climate-safe and just urban futures. However, existing scientific studies depicting future trajectories of urban water management have struggled to make the intertwined social and ecological dynamics of (transformative) urban adaptation tangible and accessible. This study focuses on the potential of visual communication of scenarios to stimulate both learning among scientists (during the process of creating the scenarios) and social learning (as a next step using the developed “narrative images”) to motivate diverse societal actors to engage with the complexity of sustainable urban water management. Art can overcome barriers of scientific and technical concepts and touch peoples' inner motivation for preserving and sustainably transforming our cities in a way that written texts cannot. As sustainability challenges transcend disciplines, this study draws methodically on an interdisciplinary scenario approach. Three adaptation scenarios were developed in a participatory process and professionally visualized as “narrative images” using the city of Hamburg as a case study. The scenarios take place in 2050 depicting a gradient ranging from coping to incremental adaptation to transformative adaptation for managing the water-adaptation nexus: “Water defensive city,” “Water resilient city,” and “Water aware city.” The scenario study shows innovatively how to bring the humanities, natural and engineering sciences into a deliberative dialog, while at the same time promoting collective learning. It can serve as a model for successful future interdisciplinary research and scenario developing exercises.